Pengaruh Teknik Distraksi Menonton Kartun Animasi Terhadap Skala Nyeri Anak Usia Prasekolah Saat Pemasangan Infus di Instalasi Rawat Inap Anak RSUP DR.M. DJAMIL PADANG: The Effect of Distraction Techniques Watching Animated Cartoons on the Pain Scale of Preschool Age Children During Infusion Installation at the Pediatric Inpatient Installation of Dr.M. DJAMIL PADANG Hospital - Rika Sarfika; Nova Yanti; Ruspita Winda (Fakultas Keperawatan Universitas Andalas, 2015)
Intravenous cannulation is invasive procedure that cause pain for children. One of nonpharmacological technique easy to be done, can do by nurse, and theoretically effective to reduce pain whenchildren undergoing invasive procedure is animated cartoon. The purpose of this study was determined the effectof animated cartoon strategy of the pain scale when preschool children undergoing intravenous cannulation.The data was collected since September-October 2014 in RSUP DR.M.Djamil Hospital Padang used quasyexperimental with the posttest only with control group design. The sampling technique used consecutivesampling with sample of 22 preschool children (2-6 year). 11 people in an experimental group, and 11 people ina control group. Pain was measured directly by using FLACC ((Face, Legs, Activity, Cry, Consolability) Scale.Data analysis was done with the Mann-Whitney test to assess difference in pain between the experimental groupand the control group. The results of the study showed that there is significantly (p<0,05) different of mean painscale between children gived animated cartoon distraction and children not gived animated cartoon distractionduring intravenous cannulation. This research is recomended for nurses and health care to apply watchinganimated cartoon distraction as non-pharmacological technique when intravenous cannulating for low painscale of children.